On the history and future of soil organic phosphorus research: a critique across three generations. (5th January 2018) - Haygarth, P. M.; Harrison, A. F.; Turner, B. L.
Summary: Soil organic phosphorus has broad agronomic and ecological significance, but remains a neglected topic of research. This opinion paper reflects a collaborative discussion between three generations of scientists who have collectively studied soil organic phosphorus for almost 50 years. We discuss personal reflections on our involvement in the field, opinions about progress and promising opportunities for future research. We debate an apparent overemphasis on analytical methodology at the expense of broader questions, and whether this has stifled progress in recent decades. We reiterate the urgent need to understand organic phosphorus cycling in the environment to address fundamental questions about phosphate supply, crop nutrition, water quality and ecosystem ecology. We also contend that we must encourage and integrate the study of organic phosphorus across all scales, from molecular chemistry to global cycling. Our discussion among three generations of researchers shows the value of a long‐term perspective, emphasizes the changing nature of this field of research, and reinforces the importance of continuing to be curious about the dynamics of organic phosphorus in the environment. Highlights: Critical evaluation of the current state of soil organic phosphorus research Collective views of three researchers whose careers span 50 years Research is driven by analytical development, but will benefit from broader conceptual approaches We emphasize the value of long‐term and broad‐scale perspectives on this important research topic